Country-of-origin effects in industrial goods markets: Do country-of-origin image effects differ for different buying center members? - Michael Justus Reichert; Claudia Fantapié-Altobelli (jbm - Journal of Business Market Management, 2016)
Most of the past findings regarding COO (country-of-origin) effects refer to consumer decision-making. While their purchase decisions are taken by the consumers themselves individually, industrial purchases are mostly conducted by organizational buying centers. This raises the question if and to what extent the impact of COO effects varies between the different members of a buying center - an issue unaddressed in research so far. Based on construal level theory we answer this question by applying a multiple mediation analysis to the empirical data, which we collected through interviews at a truck trade show. Main findings confirm the general relevance of COO effects for the purchase decision making for these industrial goods. However, the significance of this COO effect was found to be of lesser importance for product users than for non-users. On the basis of our findings, practitioners can achieve higher marketing impact through the differentiation of their marketing activities.
urn:nbn:de:0114-jbm-v9i2.1603
Keywords: 650; Internationalization; Mediation; Country-of-Origin; Industrial Goods; Business-to-Business; Buying-Behavior